1993
DOI: 10.1073/pnas.90.21.10380
|View full text |Cite
|
Sign up to set email alerts
|

Central oxytocin inhibition of salt appetite in rats: evidence for differential sensing of plasma sodium and osmolality.

Abstract: Sodium chloride ingestion is stimulated during conditions of sodium deficiency to maintain body fluid and electrolyte balance. Recent studies have indicated that salt appetite in rats is often inversely related to peripheral and central secretion of the hormone oxytocin (OT). We studied the potential role of central OT on salt and water ingestion by treating rats intracerebroventricularly with OT conjugated to the A chain of the plant cytotoxin ricn (rAOT) to produce a chronic selective inactivation of brain c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 22 publications
4
50
0
Order By: Relevance
“…21 These results are supportive of studies in rats that showed that PEG-induced salt intake was inhibited by central OT administration, 9 whereas lesions of the brain OT system increased the response to hyperosmolality. 11 In contrast, an OT antagonist had no effect on PEGinduced salt intake. 9 Studies that compared the effect of volume expansion with hypertonic mannitol versus saline showed that saline intake was responsive to osmolality changes, rather than sodium.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…21 These results are supportive of studies in rats that showed that PEG-induced salt intake was inhibited by central OT administration, 9 whereas lesions of the brain OT system increased the response to hyperosmolality. 11 In contrast, an OT antagonist had no effect on PEGinduced salt intake. 9 Studies that compared the effect of volume expansion with hypertonic mannitol versus saline showed that saline intake was responsive to osmolality changes, rather than sodium.…”
Section: Discussionmentioning
confidence: 98%
“…9 Studies that compared the effect of volume expansion with hypertonic mannitol versus saline showed that saline intake was responsive to osmolality changes, rather than sodium. 11 To proceed to the next stage, we determined whether a stimulus to volume receptors alters salt intake in mice and whether the response is changed in the OT gene-disruption model. Volume depletion with PEG has become a standard test model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxytocin release in the brain seems to parallel the secretion of this hormone into the blood, and oxytocin in both systems is activated by similar stimuli, including ANG II (12,45,46,123). However, the oxytocin found and released in the CNS inhibits sodium appetite (12)(13)(14)(121)(122)(123)(124). Intracerebroventricular (icv) injections of oxytocin reduce sodium intake (12)(13)(14), and central delivery of an oxytocin receptor antagonist, or the destruction of brain neurons containing oxytocin receptors by oxytocin conjugated to the cytotoxin ricin, increase hypertonic NaCl intake in rats treated with a central injection of ANG II (12,123).…”
Section: Major Neurohumoral Factors Inhibiting Water And/or Sodium Inmentioning
confidence: 99%
“…In contrast, blood volume expansion releases humoral factors, such as atrial natriuretic peptide (ANP), which inhibit salt and water intake (5,6,14,49). Other agonists and receptor subtypes, such as oxytocin and ␣ 2 -adrenoceptors, act in the brain to inhibit behavioral responses that expand body fluids (12,13,39,40,48,93,123,125).ANG II and hyperosmolarity act on sites that function as sensory structures, specifically the OVLT, SFO, and AP, which are located outside the blood-brain barrier. In some cases they also act on structures located within the blood-brain barrier such as the supraoptic nucleus of the hypothalamus (25, 26, 75-77, 84, 86, 118, 119).…”
mentioning
confidence: 99%